2015
DOI: 10.1039/c5py01451d
|View full text |Cite
|
Sign up to set email alerts
|

Successful radical induced cationic frontal polymerization of epoxy-based monomers by C–C labile compounds

Abstract: Thermal bulk curing of epoxy resins is a non-energy efficient method. On the other hand classical photocuring techniques for epoxy resins are limited to quite thin layers, due to the limited penetration depth of UV-light. We show that Radical Induced Cationic Frontal Polymerization (RICFP) is a promising technique for the energy efficient bulk curing of epoxy resins. The combination of a C-C labile compound (1,1,2,2tetraphenylethanediol) as a thermal radical initiator with diaryliodonium salts results upon loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
133
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(133 citation statements)
references
References 22 publications
0
133
0
Order By: Relevance
“…The reaction mechanism of RICFP for epoxy resins was first described by Mariani et al [15] and following deeply investigated by Bomze et al [16] It was shown that the FP is started by the dissociation of a radical thermal initiator (RTI) promoted by the heat released during surface UVinduced cationic ring-opening polymerization. Subsequently, the carbon-centered radicals are oxidized to carbocations by the presence of the iodonium salt PAG (On + in Figure 1) in a RICP mechanism.…”
Section: Doi: 101002/macp201700313mentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction mechanism of RICFP for epoxy resins was first described by Mariani et al [15] and following deeply investigated by Bomze et al [16] It was shown that the FP is started by the dissociation of a radical thermal initiator (RTI) promoted by the heat released during surface UVinduced cationic ring-opening polymerization. Subsequently, the carbon-centered radicals are oxidized to carbocations by the presence of the iodonium salt PAG (On + in Figure 1) in a RICP mechanism.…”
Section: Doi: 101002/macp201700313mentioning
confidence: 99%
“…Subsequently, the carbon-centered radicals are oxidized to carbocations by the presence of the iodonium salt PAG (On + in Figure 1) in a RICP mechanism. The most recently developed system is based on the RTI tetraphenylethanediol (TPED, benzopinacol), the iodonium salt PAG p-(octyloxyphenyl)phenyliodonium hexafluoroantimonate (IOC-8 SbF 6 ) and the commonly used epoxy monomer bisphenol-A diglycidyl ether (BADGE) [16] (Figure 2).…”
Section: Doi: 101002/macp201700313mentioning
confidence: 99%
See 1 more Smart Citation
“…As example, the decrease of light penetration with increasing thickness represents a serious drawback for thick, pigmented coatings and fiber-reinforced composites. Therefore, the concept of dual-cure initiating systems based on both photo-thermal curing appears as a promising alternative to solve the issue [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Indeed, the combination of a photochemical polymerization promoting a thermal curing has rendered possible the curing of thick samples.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the thermal process can also be used to complete the curing of the epoxide resin in shadowed areas, typically in the case of 3D parts. In the best cases, the photochemical process would also speed up the thermal curing to perform a photoinduced thermal frontal polymerization [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%